Improvements of the Starting Performance of A Novel Brushless Doubly-fed Motor Based on the Composite Coils - Zhiwei Ruan; Chaohao Kan; Chenglong Chu; Taian Ren; Qiuming Chen (Energies, 2019)
Brushless doubly-fed motor (BDFM) has well applicable potentials in the speed control driving field due to its excellent speed regulation performance. However, the poor starting performance becomes a shortage that still limits the development and application of wound BDFM. To solve the problem, this paper presents a novel BDFM adopted rotor winding based on the principle of the composite coil. Both the principle of the composite coil and the designed example of the rotor winding are analyzed in detail in this content, and the stator winding designed by the change-pole method is described. The performance of the prototype was tested by simulation and experiments, both results reveal that this method can effectively improve the starting performance of BDFM, the system is simplified, and the stability of it is prompted.